(untitled) (Bangladesh Journal of Nuclear Medicine, 2021)
Background: Whileradioactive iodine therapy (RAIT) in patients with primary hyperthyroidism results in euthyreosis or hypothyreosis, requirement of repeated therapy in a proportion of patients is a clinical reality. This study describesbiochemical outcomeof patients requiring repeated RAIT and the dose profiles across the demographic traits. Patients and Methods: The study retrospectively included the patients who underwent RAIT for Primary hyperthyroidism from January to December of 2006, using a modified fixed dose protocol following an institutional guideline which was adopted as the national guideline in 2007. Persistence of biochemical features of hyperthyroidism six months after RAIT was an indication for repeated therapy. Follow up data of eligible patients till December of 2016 was included in the descriptive statistics. Results: One, Two, three and four instances of RAIT were given to 83%, 14%, 2% and ≤ 1% of patients resulting in hypothyroidism to 58%, 67%, 67% and 100% of patients after each instance of therapy with incremental dose. Apparently more females than males ended up as biochemically hypothyroid, though not significant (OR 1.15, p=0.56).Younger females became significantly hypothyroid (p = 0.03).Patients with euthyroid outcome received higher dose-1of RAIT (P=0.007) which was found significant in females (p=0.005), in patients with Graves’ disease (GD) (p=0.018) and in patients receiving two instances of RAIT (p=0.03). Among the patients with GD, Single Toxic Nodule (STN) and Multi-Nodular Goiter (MNG), the proportion of hypothyroid outcome were 61%, 67% and 35%, at ten years following first dose. GD and STN required RAIT for up to four instances.MNG received an apparently higher mean of dose -1 and apparently less steep increment of doses, in comparison to GD and STN. Conclusion: Thisobservationof patient outcome over a decade was a scope to compare the mentioned guideline’s performance with the targets set by influential guidelines and recent reports around the globe. Bangladesh J. Nuclear Med. 22(2): 119-124, Jul 2019